The JAK2/STAT5 signaling pathway as a potential therapeutic target in canine mastocytoma. (11th April 2017) - Keller, Alexandra; Wingelhofer, Bettina; Peter, Barbara; Bauer, Karin; Berger, Daniela; Gamperl, Susanne; Reifinger, Martin; Cerny‐Reiterer, Sabine; Moriggl, Richard; Willmann, Michael; Valent, Peter; Hadzijusufovic, Emir
Abstract : Background: Mastocytoma are frequently diagnosed cutaneous neoplasms in dogs. In non‐resectable mastocytoma patients, novel targeted drugs are often applied. The transcription factor STAT5 has been implicated in the survival of human neoplastic mast cells (MC). Our study evaluated the JAK2/STAT5 pathway as a novel target in canine mastocytoma. Materials and Methods: We employed inhibitors of JAK2 (R763, TG101348, AZD1480, ruxolitinib) and STAT5 (pimozide, piceatannol) and evaluated their effects on 2 mastocytoma cell lines, C2 and NI‐1. Results: Activated JAK2 and STAT5 were detected in both cell lines. The drugs applied were found to inhibit proliferation and survival in these cells with the following rank‐order of potency: R763 > TG101348 > AZD1480 > pimozide > ruxolitinib > piceatannol. Moreover, synergistic anti‐neoplastic effects were obtained by combining pimozide with KIT‐targeting drugs (toceranib, masitinib, nilotinib, midostaurin) in NI‐1 cells. Conclusion: The JAK2/STAT5 pathway is a novel potential target of therapy in canine mastocytoma.